EFFECTS OF PROPOFOL AND SEVOFLURANE ON METABOLIC CHANGES AND OXIDATIVE STRESS MARKERS IN LAPAROSCOPIC APPENDECTOMY IN CHILDREN: CLINICAL CONTROL TRIAL: Stress markers in pediatric appendectomy - Fabri Galambos, Izabella (Journal of Medical Biochemistry, 2025)
Background: Laparoscopic appendectomy offers several advantages over open surgery, including shorter recovery time and less postoperative pain. However, it also poses some risk due to the creation of pneumoperitoneum. Understanding and mitigating this risk through the use of appropriate anesthetic agents, antioxidant therapy, and optimized surgical techniques can improve patient outcomes. The aim of this study was to determine which of the two anesthetics, propofol or sevoflurane, provides better suppression of oxidative, inflammatory and metabolic responses in children undergoing laparoscopic or conventional appendectomy.Methods: This prospective, clinical observational study enrolled 120 children aged 7 to 17 years with a diagnosis of acute appendicitis. Key parameters, including blood glucose, white blood cells, IL-6, oxidative stress markers, lactate, pH, and mean arterial pressure, were analyzed.Results: A statistically significant change in lactate and mean arterial pressure values was observed over time in all four study groups. However, neither the type of surgical procedure nor the type of anesthesia significantly influenced glucose, white blood cells or thiobarbituric acid levels. The postoperative values of IL-6 were lower in patients treated with balanced anesthesia.Conclusions: Our study demonstrated that the type of anesthesia affects hemodynamic changes, which are closely related to the occurrence of reperfusion injury. Although markers of tissue hypoxia and acidosis were elevated during laparoscopic surgery, their values quickly normalized in the immediate postoperative period. Keywords: appendectomy; laparoscopy; pediatric anesthesia
Keywords: appendectomy; laparoscopy; pediatric anesthesia